Going to the Dogs and Finding New Hope: An intra-species collaboration - Dwan, Maeve (Murmurations: Journal of Transformative Systemic Practice, 2025)
In my own attempt to further a refusal of binary dualisms and embrace and embody the potential of this often messy collaboration with otherness, I attempt to explore a meeting in time and space with a young person, myself as a not so young therapist and canine co-therapist. What I offer are my reflections and thoughts and what I imagine to be Holly the dog’s reflections. I wonder how we might be generating new knowledge in practice as we come together in this canine human emergent practice of co-travel. This one small story of intra-species collaboration is not necessarily a new ontology or ideology in of itself. What I wish to highlight are ideas of becoming through an intra-species collaboration of love and hope. I describe some of my thoughts and experiences as I begin a journey with Holly as co-therapist in my work with young people. I explore how the discarding of typological thinking and being open to a movement beyond binary dualisms can enrich clinical practice.